(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the exploration of ecological themes in Indian English drama, examining how playwrights utilize dramatic elements to address environmental concerns. The paper investigates the portrayal of ecological issues, the representation of nature, and the socio-cultural implications depicted in select Indian English plays. By employing a combination of literary analysis and ecological criticism, this study aims to highlight the significance of ecological consciousness in Indian English drama, contributing to a deeper understanding of environmental narratives within the context of Indian literature and culture.